Aquatic space activities - Praxis needs theory - Ungerechts, B.; Klauck, J. (1st International Scientific Conference of Aquatic Space Activities, 2008)
Aquatic Space Activities (ASA) is an umbrella-like term for activities in water like: Competitive - Recreational - Masters swimming, Fin-swimming, Triathlon, Scuba-diving or Water-exercises. ASA have to obey flow physics. Traditionally, flow physics in aquatic sports is confined to steady conditions assuming that the flow velocity is constant and the body is rigid. It is not new information that this is not and was never the case in human swimming. Fact is, limbs change motion in all ASA which cause unsteady flow conditions. Unsteady flow demands closer consideration of water-motion induced by limbs` motion. The purpose of this paper is to introduce some challenging information concerning unsteady flow conditions and consequences for practise.